The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1127/nova_hedwigia/2019/0560
|View full text |Cite
|
Sign up to set email alerts
|

Myxomycetes associated with mountain tropical forests of Bidoup Nui Ba and Chu Yang Sin national parks (Dalat Plateau, southern Vietnam)

Abstract: A systematic survey for myxomycetes was carried out in 2011–2014 and 2017 at 106 localities in mountain tropical forests of Bidoup Nui Ba and Chu Yang Sin national parks (Dalat Plateau, southern Vietnam). In total, the survey yielded 652 records, of which 358 were field collections and 294 were collections obtained from 819 moist chamber cultures prepared with samples taken from the bark surface of living trees, ground and aerial litter and coarse woody debris. Determinations resulted in 105 taxa from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(4) LOW INPUT: Taxonomically critical material is often very scanty, especially specimens from moist-chamber cultures which are crucial for surveys in arid (Schnittler et al 2015b) and tropical regions (Novozhilov et al , 2019. Therefore, one needs to obtain material for sequencing without destroying a sporocarp.…”
Section: Discussionmentioning
confidence: 99%
“…(4) LOW INPUT: Taxonomically critical material is often very scanty, especially specimens from moist-chamber cultures which are crucial for surveys in arid (Schnittler et al 2015b) and tropical regions (Novozhilov et al , 2019. Therefore, one needs to obtain material for sequencing without destroying a sporocarp.…”
Section: Discussionmentioning
confidence: 99%
“…This species is initially considered as truly coprophilous, which is known from very few collections in the world. Novozhilov et al (2020) first reported this species for the county and that is also noteworthy to mention that the species Trichia pappilata is only reported in Vietnam in comparison among other countries in the Southeast Asian region.…”
Section: Myxomycetes Occurrences In Leaf Litter Of Northern Vietnammentioning
confidence: 96%
“…Some previous countries in the region that have information for myxomycete studies are the Philippines with 159 species (Dagamac and dela Cruz 2015;Macabago et al 2017;Bernardo et al 2018), Thailand with 145 (Ko Ko et al 2010;Dagamac et al 2017b), Indonesia with 119 (Farr 1990;Rosing et al 2011), Republic of Singapore with 76 (Rosing et al 2011), Myanmar with 67 (Ko Ko et al 2013a), and Laos with 44 (Ko Ko et al 2013b). In Vietnam, most of the myxomycete studies have been investigated in the southern part of the country (Novozhilov et al 2018(Novozhilov et al , 2020 while the number of myxomycete studies on the other parts of the country is relatively scarce. Furthermore, the first myxomycete report for Vietnam started only in 2009 that initially annotated 23 species by Van Hooff (2009), wherein the rare species Cribraria tecta was reported as a new species for science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the first local habitat suitability modeling using the tropical cosmopolitan species Diderma hemisphaericum (Bull) Hornem has demonstrated range expansion of the species on various climate change scenarios (Almadrones-Reyes & Dagamac 2018). Recently, the Paleotropical Asia-Pacific zone had also gained its momentum of more exhaustive myxomycete surveys wherein Southeast Asian countries like Vietnam (174 species, Nguyen et al 2019, Novozhilov et al 2020 and Thailand (145 spe Stephenson (Novozhilov & Stephenson 2015)]. To contribute to this growing trend in myxomycete distribution studies, the primary objective of the present study was to investigate the assemblages of myxomycetes in two lowland forests of Mindoro Island.…”
Section: Introductionmentioning
confidence: 99%